Synthesis of Cu-PTC (Perylene 3,4,9,10-tetracarboxylate) Metal-Organic Framework (MOF) for Methylene Blue Photodegradation - Farhah Syahidatul Mala; Siti Nurbayti; Adawiah Adawiah; Agustino Zulys; Nanda Saridewi (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Disposal of synthetic dye waste, including methylene blue, has been increasing in recent years. The photocatalytic method is an effective approach for degrading dyes, using Metal–Organic Frameworks (MOFs) as catalysts and light as the energy source. This study aims to synthesize Cu-PTC MOF as a photocatalyst and evaluate its performance in degrading methylene blue dye. Cu-PTC was synthesized using Cu(NO3)2.3H2O and perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) via a solvothermal method. The resulting MOF was characterized using X-ray Diffraction (XRD), Ultraviolet–Visible Diffuse Reflectance Spectroscopy (UV-Vis DRS), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy (SEM). Cu-PTC exhibits a bandgap energy of 1.72 eV and characteristic functional groups at wavenumbers 1689 cm-1 (C=O), 1590 cm-1 and 1360 cm-1 (-COO), 3450 cm-1 (O-H), and 738 cm-1 and 654 cm-1 (Cu-O). The Cu-PTC MOF has a crystallinity degree of 85.35%, a crystal size of 35.33 nm, and a rod-like surface morphology. Under visible light irradiation, it achieves an optimum degradation efficiency of 71.45%, with an adsorption capacity of 73.28 mg/g for methylene blue dye at a concentration of 50 ppm, using 25 mg of Cu-PTC MOF at pH of 7 over a period of 60 minutes. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).